A Tumor‐Organoid‐Based Precision Medicine Platform for the Prediction of Drug Sensitivity of Colorectal Cancer (Adv. Therap. 12/2022). Issue 12 (14th December 2022) - Wang, Xingyue; Lu, Xiaohuan; Cai, Bo; Li, Xiaoqiong; Zou, Danyi; Lei, Shijun; Xu, Luming; Wang, Guobin; Wang, Lin; Wang, Zheng
Abstract : Investigation of clinical actionable targets is crucial for the individual treatment of patients with advanced colorectal cancer. The picture represents an integrated precision medicine approach which combines high‐throughput sequencing platform with a microfluidic organoid drug testing system. It provides a novel insight to precision medicine for colorectal cancer patients. This is reported by Guobin Wang, Lin Wang, Zheng Wang, and co‐workers in article 2200093 .